ANALYSIS OF SHAKESPEARE’S LEAR’S REGENERATION IN KING LEAR - HIDAYAH NOR; NUR LAILATUR ROFI'AH (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2018)
The aim of this research is to describe: 1) The character of Lear in Shakespeare’s King Lear, 2) How Lear gains the regeneration and self education about his environment, 3) Assessing the divine dispensation in Lear’s tragedy. This research is qualitative method. Qualitative method is a research procedure that results in description data in the form of words. The data of this research is King Lear a play by Shakespeare. This research used intrinsic approach. Technique of collecting data is used by reading the play and analyzing the play. The technique of analyzing data is using content analysis of three elements, which are reading the data, presenting data and analyzing. Based on the result of the research can be concluded: 1) Lear’s character win the initial play was arrogant, self-deceived, and powerful. 2) Lear struggles to gain the education of his environment must undergo several predicaments in his life including betrayal by his own daughter, expelled from his kingdom, going madness and exposed through the storm. 3)